1994
DOI: 10.1007/bf00180228
|View full text |Cite
|
Sign up to set email alerts
|

The Nepalese patuka in the prevention of back pain

Abstract: The patuka is a special piece of cloth worn around the waist by heavy workers and mountain porters in Nepal. An investigation was carried out to study its role in preventing pain in the back. Observations of intra-abdominal pressure and the lumbosacral compression force confirmed that the patuka might be responsible for the low incidence of back pain in those wearing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…A study through observation of intra-abdominal pressure and the lumbosacral compression force confirmed that on wearing "patuka" or lumbar supporter might be accountable for the low incidence of LBP [59]. Very few construction workers, 28.7% among those with LBP and 4.0% among those without LBP were using "patuka" to prevent or manage LBP.…”
Section: Protective Measuresmentioning
confidence: 94%
“…A study through observation of intra-abdominal pressure and the lumbosacral compression force confirmed that on wearing "patuka" or lumbar supporter might be accountable for the low incidence of LBP [59]. Very few construction workers, 28.7% among those with LBP and 4.0% among those without LBP were using "patuka" to prevent or manage LBP.…”
Section: Protective Measuresmentioning
confidence: 94%
“…17,26,27,37 Reported results in all four showed an increase in IAP, but electromyogram in the erector spinae muscles consistently decreased in only one. 27 In seven studies, investigators measured IAP but did not simultaneously record an electromyogram of the back muscles (Table 3), 15,16,24,43,42,52,62 Investigators in two of these studies reported an increase in IAP in subjects using lumbar supports, 16,52 in two studies they reported inconsistent results, 15,43 and three they found no effect of a lumbar support on IAP. 24,42,62 Separate meta-analyses for studies on electromyogram of erector spinae muscles and on IAP were conducted.…”
Section: Reduction In Back Muscle Forcementioning
confidence: 99%
“…Specialized garments to prevent back pain while carrying heavy loads date back to centuries and are present across different cultures. The Nepalese Patuka is a garment worn around the waist to aid in load bearing and has shown some modest efficacy in preventing back pain in mountain porters ( 13 ). More recently, the use of a load-bearing vest and thigh holster resulted in less discomfort in the Swedish police ( 14 ) and in a randomized crossover study, exosuits showed favorable results of pain reduction compared to the control conditions in surgeons ( 15 ).…”
Section: Prevention Of Clothing or Footwear-induced Pain In The Gener...mentioning
confidence: 99%